OPERATIONAL CHALLENGES AND STRATEGIC SOLUTIONS FOR POWER DISTRIBUTION IN MENDOL ISLAND - Priasmoro, Dalie
The growing energy demands and the need for a reliable power supply on Mendol Island have underscored significant operational and financial inefficiencies at the Teluk Dalam Diesel Power Plant. These inefficiencies manifest in the plant's inability to meet peak power demands reliably, high operational costs due to excessive fuel consumption, and restricted operational hours, all of which adversely affect customer satisfaction and trust. Consequently, there is an urgent necessity for a comprehensive analysis of these challenges to formulate strategic interventions aimed at enhancing the plant's operational capacity, reliability, and financial sustainability.